2015
DOI: 10.1002/ijc.29414
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine is a safe antiangiogenic drug which can also prevent 5-fluorouracil induced neutropenia

Abstract: The role of vascular endothelial growth factor - A (VEGFA) in tumor angiogenesis is well established and accordingly, molecules targeting VEGFA or its receptors are being presently used in the clinics for treatment of several types of cancer. However, these anti-angiogenic agents are expensive and have serious side effects. Thus identification of newer drugs with manageable systemic side effects or toxicities is of immense clinical importance. Since we have reported earlier that dopamine (DA) inhibits VEGFA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 24 publications
(74 reference statements)
3
42
0
2
Order By: Relevance
“…The anti-Parkinsonian drug dopamine was recently reported to inhibit vascular endothelial growth factor A (VEGFA) and tumor angiogenesis (50), thus possibly lowering cancer risk. In the current study only a small number of patients were treated solely with dopamine, however patients that were treated with dopamine agonists or other medical combinations that contain dopamine did not have statistically significant lower CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-Parkinsonian drug dopamine was recently reported to inhibit vascular endothelial growth factor A (VEGFA) and tumor angiogenesis (50), thus possibly lowering cancer risk. In the current study only a small number of patients were treated solely with dopamine, however patients that were treated with dopamine agonists or other medical combinations that contain dopamine did not have statistically significant lower CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine receptors (DRD1-5) mainly reside in the human brain, which play important roles in cancer tumorigenesis and progression [5][6][7][8][9]. DRD2 agonists inhibit the growth of lung cancer cells including NSCLC and small cell lung cancer [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the treatment of PD may provide another explanation. Dopamine, which is a drug used in the therapy for PD, was reported to be an effective anti-angiogenic drug for the treatment of malignant tumors [23], thus it may decease the risk of lung cancer. Indeed, our result indicated that the significant inverse relationship between PD and risk of lung cancer could be found in after PD group, but could not be found in before PD group.…”
Section: Discussionmentioning
confidence: 99%